Biostratigraphy and paleobiogeographic affinities of the Jurassic brachiopod assemblages from Sierra Espuña (Maláguide Complex, Internal Betic Zones, Spain) - Baeza-Carratalá, J.F.; García Joral, F.; Tent-Manclús, J.E. (Journal of Iberian Geology, 2011)
The assemblages of Early Jurassic brachiopods (Pliensbachian - Toarcian) from Sierra Espuña (Murcia Province, SE Spain) are described. This is the only area in the Internal Zones of the Betic Cordillera, corresponding to the margins of the Alborán Terrane, where Jurassic brachiopods are known to occur. In the tectonic Unit of Morrón de Totana (more southward located) assemblage MT1 of Late Pliensbachian age has been characterized. This assemblage has been subdivided into three successive sub-assemblages: MT1a (Algovianum Zone), MT1b (Emaciatum Zone, Solare Subzone) and MT1c (Emaciatum Zone, Elisa Subzone). Northward, in the Perona tectonic Unit two distinct assemblages, P1 (Latest Sinemurian - Early Pliensbachian) and P2 (Early Toarcian, Serpentinum Zone) have been recognized. Differences between the assemblages from the two tectonic units are evident after the paleobiogeographical analysis. In the Morrón de Totana Unit, taxa with Mediterranean affinities occur. MT1 assemblage is very similar to assemblages previously known in the Eastern Subbetic as well as in other areas of the Mediterranean Province. In the Perona Unit the Mediterranean affinity of the assemblages is not so evident. P1 Assemblage consists of widely distributed taxa, lacking in the most characteristic elements of the Mediterranean Province which, however, are present in neighbouring Betic areas. P2 Assemblage belongs to the Spanish Province that develops in Western Tethys after the Early Toarcian Mass Extinction Event. The occurrence in this assemblage of Prionorhynchia aff. msougari Rousselle, until now only found in North Africa, indicates a closer connection of the Perona Unit with the African paleomargin of the Tethys than with the South Iberian paleomargin. The paleobiogeographical data suggest a more southern and marginal (close to epicontinental areas) position of the Perona Unit than the Morrón de Totana Unit.